AN EXPERIENCE TO ENCOURAGE STUDENTS’ WRITING SKILL THROUGH MULTIMODALITY (2022)
Creative writing provides new options for students to motivate English language learning allowing them to use it meaningfully to interact with the world. Thus, this research experience attempts to integrate multimodality principles into creative writing as an opportunity to encourage eighth graders’ EFL learning at a public institution in Tunja. This research project follows action research features where a pedagogical intervention is conducted: four workshops were designed conveying creative writing activities using simultaneously image, video, text, sound, speech. Afterwards, they were uploaded to EDMODO learning space. Instruments used were surveys, students’ artifacts and focus groups. A process of planning, testing, observing and reflective cycle was followed. Data collected was analyzed following the grounded theory approach. Results indicate that by integrating creative writing along multimodality and E-learning environments, English learning becomes meaningful for them as a means of real self-expression and communication during the Covid-19 pandemic; their motivation is enacted when English permeates digital spaces in order to share thoughts and ideas in a creative way by using songs, pictures, drawings, and their own voice along their texts. Therefore, multimodal creative writing activities in virtual spaces demonstrate to be joyful strategies to foster motivation to learn and use English language, and they can be applied in the upcoming future in online and hybrid EFL classrooms.